The influence of meteorological factors on the production of maize crop in the South-Muntenia region - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The impacts of climate change on the area's agricultural potential and their economic and social effects on sustainable development in the environment are a topical and future issue. The paper aims at assessing the potential areas in the South-Muntenia Region, identifying, quantifying and qualitatively analyzing climatic parameters such as precipitation, maximum and minimum air and humidity temperatures, measured during the period 2013-2017 for maize crops for see their influence on productions and deliver optimal solutions. The statistical indicators that characterize the average crop production and the correlation coefficients between them and the main climatic parameters that influence the culture concerned will be calculated.
Keywords: Q1; Q15; Q54; 330; climatic factors; average production; parameters